Warranties, Durability, and Maintenance: Two-sided Moral Hazard in a Continuous-Time Model - Dybvig, Philip H.; Lutz, Nancy A. (Review of Economic Studies, 1993)
Double moral hazard in continuous time generates the familiar warranty pattern with full coverage for an initial block of time. The more complete the warranty, the better the producer's durability incentives and the worse the consumer's maintenance incentives. Using continuous time highlights the need for some warranty bound to avoid reaching the first-best as an unreasonable limit. Early in the paper, an exogenous bound is used, while later the bound arises endogenously from the possibility of abuse and repair. A quadratic example shows that the warranty's duration depends on the relative severity of the two moral hazard problems.